Eunotia itacueretabaensis sp. nov. (Bacillariophyceae, Eunotiaceae) from the Campos Gerais region, Southern Brazil - Bartozek, Elaine C. R.; Tremarin, Priscila; Peres, Cleto K.; Branco, Ciro C. Z. [UNESP] (Magnolia Press, 2020)
We describe a new periphytic eunotioid species, Eunotia itacueretabaensis sp. nov., found in a second order stream in Vila Velha State Park in Southern Brazil. We analyzed both size variation and external and internal morphological features under light and scanning electron microscopy. The new species is mainly characterized by large size and morphology variation, and by the presence of three slight undulations in the dorsal margin of the valve in larger individuals, while smaller ones feature a single undulation, making it distinct from other known species. Its morphology is compared with similar species, as Eunotia pectinalis and Eunotia silvae. Eunotia itacueretabaensis was found attached to submerged tree trunks and forming macroscopic colonies in a fast flow acidic stream. Besides representing a new addition to the present database of Brazilian diatom flora, our study highlights the important role of environmental conservation areas, which serve as important repositories for unexplored species.
Keywords: Araucaria Forest; diatom; Parana state; taxonomy